Hubungan Faktor Lingkungan dengan Penggunaan Trihexyphenidyl pada Remaja di BNN Kota Surabaya - Indri Riza Priescisila; Mahmudah Mahmudah (Universitas Airlangga, 2016)
Drugs abuse is increase every years. One of the type of medicines that often abused by teenager is trihexyphenidyl or commonly called pills koplo. The use of a drug was infl uenced some of factors, such as environment (schools, family, and their peers). The purpose of this research to fi nd out the relationship between environment factors with the use of trihexyphenidyl by teenager in BNN Surabaya City. The research was observational research by design cross sectional. Technique sampling the research is simple random sampling, from teenager was 12-21 years and used trihexyphenidyl who performs outpatient in BNN Surabaya City as many as 48 people. The research was done at September 2015-Januari 2016 in BNN Surabaya city. The results showed that 52,1 percent teenager was 12-15 years old and male (66.7 percent). Half of teenager had completed their junior high school of 62.5 percent and the parents of teenagers work as a private employees. The most teenagers 54,2 percent used trihexyphenidyl among 1-3 years. Teenager stop using trihexyphenidyl were 62.5 percent. The results of the chi square analysis showed that there was no correlation between schools, family, and their peers variables with the use of trihexyphenidyl by teenager in BNN Surabaya City .The usage of trihexyphenidyl among teenager not only caused by several factors individual and their peers factors, but there are still many other reasons. The program intervention required to address the problems is providing information about danger of drugs usage or abuse medicines to teenager or the Surabaya community.